Civil and Military Airworthiness: Recent Developments and Challenges - Kourousis, Kyriakos I. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Airworthiness, as a field, encompasses the technical and non-technical activities required to design, certify, produce, maintain, and safely operate an aircraft throughout its lifespan. The evolving technology, science, and engineering methods and, most importantly, aviation regulation, offer new opportunities and create, new challenges for the aviation industry. This book assembles review and research articles across a variety of topics in the field of airworthiness: aircraft maintenance, safety management, human factors, cost analysis, structures, risk assessment, unmanned aerial vehicles and regulations. This selection of papers informs the industry practitioners and researchers on important issues.